Thinking and acting like an eclectic school counselor - Parsons, Richard D. 4 0 16; 5 (Thousand Oaks, CA : Corwin Press, 2009)
A guide for school counselors that encourages using a mix of counseling methods for the most effective approach, shows strategies for a coherent framework, and gives examples of various models.
The school counselor as reflective practitioner -- The fundamental principles of the transtheoretical model -- The stages of change -- The processes of change -- Matching stage and process -- School counselors reflecting in and on practice -- Practice in procedural thinking.
Includes bibliographical references (p. 133-134) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Educational counseling.;Student counselors.;Educational counseling.;Student counselors; 20; 2